A combined sustainability index for electricity efficiency measures. (November 2015) - Goldrath, T.; Ayalon, O.; Shechter, M.
Abstract: One of the most substantial tools that serve decision makers in their efforts to reduce greenhouse gas emissions includes energy efficiency measures that in most cases benefit from governmental assistance for achieving electricity consumption reduction goals. This paper examines five energy efficiency measures, defining a combined sustainability index. A multi-criteria analysis of five predefined indices was developed (economic, environmental, technology, social and political), providing a combined index for each measure and a tool for identifying the preferred measure within a specific situation, based on its total sustainability score. In this research, a case study was conducted and the preferred measure was found to be municipal street lighting systems, based on its high political and social scores, and its relatively high installation potential. The second choice would be replacement of chillers in the industrial sector, and the least favorable measure is the replacement of water pumps in the water sector. The methodology described brings into account the technological specifications of the measure implemented, and the specific national conditions under which it is implemented. Highlights: A MCDA of five indices was developed to define a combined sustainability index. Criteria defined were environment, technology, economy, social and political. Five energy efficiency measures were rated, based on their total sustainability score. Measures were in five main electricity consumption sectors. The preferred measure found in the case study was municipal street lighting systems.